The Effects of Customer Review on Consumer Purchase Behavior on Selected Food Establishments in Novaliches, Quezon City: A Basis for Customer Reference: Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today’s digital age, consumers wield unprecedented power in spending decisions, thanks to the influence of online reviews, providing them a voice to share experiences and impact purchasing choices. Consumers face challenges in purchasing decisions for various food establishments, such as last-minute buying without a plan, relying on recommendations, and routine shopping without thorough research. This study aimed to examine the effects of customer reviews on consumer purchase behavior at a specific food establishment.The study utilized a descriptive method, and the respondents of this study were One hundred (100) customers from 3 food establishments in Novaliches, Quezon City. 30 respondents came from Tagpuan at Villareal, 30 respondents came from Sweetie Treats Fruit Shake Villareal, and 40 respondents came from Zsakers Philippines Villareal BranchThis study reveals that younger consumers, especially those in their early twenties, play a crucial role in shaping purchasing decisions in the food industry; online reviews are influenced by a diverse demographic, including both male and female participants with varying income levels; respondents strongly agreed that customer reviews significantly impact their buying behavior, considering factors such as reviews, feedback, and ratings, product quality, dis-assembled product, and value for money; the problems encountered include late or cold deliveries, slow service, poor customer experience, and product dissatisfaction. The study establishes a significant relationship between customer reviews and consumer purchase behavior; proposing guidelines to enhance customer reference.This study recommended encouraging diverse online reviews for informed decisions, emphasizing the influence of young consumers in the food industry and the importance of balanced opinions. Share experiences based on income for unique perspectives, stressing specific details for a broad audience. Prioritize thorough, honest reviews on aspects like product quality, disassembled products, and value for money, and address issues directly with businesses. Recognize the impact of reviews on consumer behavior and consider both positive and negative feedback for informed choices. The researchers propose guidelines to improve customer reference.
Keywords: Online Reviews; Consumer; Food Establishments